Rehearsals : the German army in Belgium, August 1914 - Lipkes, Jeff, 1950- (History., 2007)
Rehearsals is the first book to provide a detailed narrative history of the German invasion of Belgium in August 1914 as it affected civilians. Based on extensive eyewitness testimony, the book chronicles events in and around the towns of Liège, Aarschot, Andenne, Tamines, Dinant, and Leuven, where the worst of the German depredations occurred. Without any legitimate pretext, German soldiers killed nearly 6,000 non-combatants, including women and children, and burned some 25,000 homes and other buildings. For more the seventy-five years, however, charges against the German Army about the killin.